Jungen in Bildungskontexten Männlichkeit, Geschlecht und Pädagogik in Kindheit und Jugend - Budde, Jürgen; Rieske, Thomas (Studien zu Differenz, Bildung und Kultur, 2022)
Reflections on boys and education have become rare in the academic field after intense debates in the 2000s and early 2010s. Even though there is a persistently active field of pedagogical practice that addresses boys and their life situations in a gender-reflective way, results of empirical research and theoretical reflections are published only sporadically. There is a need for updating the knowledge about boys and education. Primarily, this knowledge captures the workings of ideas and norms of masculinity that are oriented toward dominance. This volume sheds light on the practical parallelism of different conceptions of masculinity in educational practice, thus contributing to a differentiation of theoretical perspectives. Based on empirical studies, the contributions address the topic in relation to early childhood and school pedagogy, vocational education, open youth work, and vocational training biographies.